(untitled) (Sains Humanika, 2012)
Real Estate Investment Trusts (REITs) are collective investment vehicles that pool money from investors to buy, manage and sell real estate assets. Malaysia is the first country in the world to issue guidelines on Islamic REITs (I-REITs) on 21st November 2005. Compared with the conventional REITs, I-REITs are prohibited to engage in certain activities that are deemed as non-permissible by shariah. There are three IREITs companies which have been listed on the KLSE board but only two of these companies will be selected in this case study, covering from year 2006 until 2009. This study evaluates the performance between Al-‘Aqar KPJ REITs and Al-Hadharah Boustead REITs in terms of their profitability, liquidity and leverage. Besides that, this study will also apply the financial ratio analysis in measuring the performance of these two REITs from their investments in different real estate portfolio. The findings of the study shows that the liquidity levels of Al-Hadharah Boustead REITs are less than Al-‘Aqar KPJ REITs. In terms of their profitability ratio, both I-REITs show profits increasing from year to year. Al- ‘Aqar KPJ REITs showed a relatively high leverage ratio and the coverage ratio for the Al-‘Aqar KPJ REITs are much lower than Al-Hadharah Boustead REITs.